2021
DOI: 10.21203/rs.3.rs-228801/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy vs. Radiofrequency Ablation for Single Small Hepatocellular Carcinoma: A Propensity-score Matching Analysis of Their Impact on Liver Function and Clinical Outcomes

Abstract: Background: Stereotactic body radiation therapy (SBRT) has high efficacy for early-stage hepatocellular carcinoma (HCC) and is expected as an accepted alternative to radiofrequency ablation (RFA). However, SBRT for HCC may cause subacute liver injury leading to negative clinical outcomes. In this study, we compared changes of liver function and prognosis after SBRT or RFA in patients with single, small HCC by using a propensity-score matching analysis.Methods: We reviewed medical records of 140 patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…As for toxicities, the rates of grade 3 or higher toxicities were not significantly different between RFA and SBRT. However, increasing mean ALBI score during 1 year after SBRT (p < 0.001) in the study by Ueno et al 21 and CP score deterioration ≥2 at 3 months in the study HEPATOLOGY RESEARCH by Kim et al 8 were reported. In RFA, no liver tissue damage is generally observed outside of the ablated region.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…As for toxicities, the rates of grade 3 or higher toxicities were not significantly different between RFA and SBRT. However, increasing mean ALBI score during 1 year after SBRT (p < 0.001) in the study by Ueno et al 21 and CP score deterioration ≥2 at 3 months in the study HEPATOLOGY RESEARCH by Kim et al 8 were reported. In RFA, no liver tissue damage is generally observed outside of the ablated region.…”
Section: Discussionmentioning
confidence: 90%
“…was excluded due to a lack of description of matching factors in their abstracts. Ultimately, six PS studies remained, 7 , 8 , 12 , 19 , 21 , 22 and among them, three were PS studies that used BCLC‐factors as a matching factor for PS analysis 7,8,21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations